Writing For an Elsewhere:: Author(ity) and Authenticity in the Texts of the First Franklin Expedition (1819-1822) - Krans, Michael (Studies in Canadian Literature / Études en littérature canadienne, 1999)
The central issue in Sir John Franklin's Journals and Correspondence: The First Arctic Land Expedition, 1819-1922 is the failure of the expedition and the loss of eleven crew members. To the explorers, the Arctic was useful only as an ideological and textual construct. They came to the Arctic intent on proving the mettle of a nineteenth-century ideology, concerned with the British reading public and the progress of their own careers. To the explorers, the Arctic was not a "place," in Heideggarian terms, but simply a "blank" space on a map. Even in John Franklin's official Narrative of a Journey to the Shores of The Polar Sea in the Years 1819, 20, 21, and 22, the land seems to resist the explorers's strategy of re-writing the Arctic in the terms of their own discourse. This resistance gives rise to a tension most notable in a series of negotiations between the explorers, the land, and the people; in fact, the land's resistance fed into the explorers' masculinist and colonialist discourse. Throughout the sequence of exploration, colonization, and cultivation, the same fundamental theme predominates: it is only through European activity that land can be redeemed from nothingness.